Who should we ask? Employer and employee perceptions of skill gaps within firms - Séamus McGuinness; Luis Ortiz (The Economic and Social Research Institute (ESRI), 2014)
Using the employer-employee matched National Employment Survey of Ireland carried out in 2006, this paper compares the skill gaps as perceived by managers and employees located within the same firm. The paper looks at the main drivers of agreement / disagreement on the perception of skill gaps and considers the extent to which the way of measuring these gap s helps to explain outcome variables such as labour costs and training expenditures. The research finds that both human resource management processes and collective bargaining arrangements are important factors in facilitating agreement of training needs. Skill gaps were found to increase average training costs and average labour costs. Finally, the evidence suggests that employee perceptions of skill gaps may be prone to higher levels of subjective bias.
Keywords: J20; J24; J50; 330; skill gaps; subjective bias; labour costs; training costs